2018
DOI: 10.1016/j.bbi.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Controversies and prospects about microglia in maternal immune activation models for neurodevelopmental disorders

Abstract: Activation of the maternal immune system during pregnancy is a well-established risk factor for neuropsychiatric disease in the offspring, yet, the underlying mechanisms leading to altered brain function remain largely undefined. Microglia, the resident immune cells of the brain, are key to adequate development of the central nervous system (CNS), and are prime candidates to mediate maternal immune activation (MIA)-induced brain abnormalities. As such, the effects of MIA on the immunological phenotype of micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 152 publications
(261 reference statements)
1
50
1
1
Order By: Relevance
“…We previously found that both MIA and microglia embryonic dysfunction modulate the early positioning of interneurons in the developing cortical plate with a subsequent mild increase in the density of PV interneurons in the murine somatosensory cortex (Squarzoni et al, 2014). These findings raise the possibility that prenatal immune challenges, including microglia deficits or MIA, which modifies microglial functioning but also a wide range of additional processes (Estes and McAllister, 2016;Smolders et al, 2018), might interfere with the developmental trajectory of PV interneurons from early stages.…”
Section: Introductionmentioning
confidence: 96%
“…We previously found that both MIA and microglia embryonic dysfunction modulate the early positioning of interneurons in the developing cortical plate with a subsequent mild increase in the density of PV interneurons in the murine somatosensory cortex (Squarzoni et al, 2014). These findings raise the possibility that prenatal immune challenges, including microglia deficits or MIA, which modifies microglial functioning but also a wide range of additional processes (Estes and McAllister, 2016;Smolders et al, 2018), might interfere with the developmental trajectory of PV interneurons from early stages.…”
Section: Introductionmentioning
confidence: 96%
“…However, failure to replicate these findings indicates that both dose and timing of MIA dictate microglial sensitivity (23). Bacterial lipopolysaccharide (LPS) is also widely used to induce MIA, although disparate effects (on maternal and offspring immune responses and behavior) of TLR-4-activating bacterial endotoxin versus synthetic double-stranded TLR-3 ligand poly I:C have been well documented and create inherent variability in the MIA literature (24)(25)(26). Three consecutive maternal LPS injections increased gene expression of proinflammatory cytokines IL-1β, TNFα, and IL-6 in mouse embryonic microglia (11).…”
mentioning
confidence: 99%
“…Maternal immune activation (MIA) in mouse dams in response to a viral mimic, Polyinosinic:polycytidylic acid (Poly IC), at GD 15 decreased microglial phagocytic function and altered behavior consistent with schizophrenia-like traits in humans, changes which were reversed using a partial microglial inhibitor, minocycline [147]. These data point to a potential critical role for microglia in persistent changes in neural function, although other studies have failed to show an impact on microglial function in MIA models [148]. This said, MIA models have typically been limited to infectious stimuli, whereas MIA is likely elicited by a broader range of environmental chemicals or stimuli, and we point to this possibility briefly in the sections that follow.…”
Section: Neuroimmune Responses and Environmental Chemicalsmentioning
confidence: 96%